2012
DOI: 10.4236/ijmpcero.2012.12008
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dependence of the New Gafchromic EBT3 Film:Dose Response Curves for 50 KV, 6 and 15 MV X-Ray Beams

Abstract: Purpose: To study and compare the dose response curves of the new GafChromic EBT3 film for megavoltage and kilovoltage x-ray beams, with different spatial resolutions. Methods: EBT3 films (lot#A101711-02) were exposed to each x-ray beam (6 MV, 15 MV, and 50 kV) at 7 dose values (50-3200 cGy). Each film piece was scanned three consecutive times in the center of Epson 10000XL flatbed scanner in 48-bit color at two separate spatial resolutions of 75 and 300 dpi. The data were analyzed using ImageJ and, for each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 19 publications
4
82
1
3
Order By: Relevance
“…The local film uniformity uIlocal was measured by evaluating the SD of pixel values on the ROI analyzed for dosimetry. We found that SD linearly increased with decreasing exposure and was between 0.32 and 0.85%, which is comparable to previous studies . Intra‐film uniformity uIuniformity was evaluated to be between 0.22 and 0.45% by comparing the MPV of small films irradiated to the same dose and coming from the same sheet.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The local film uniformity uIlocal was measured by evaluating the SD of pixel values on the ROI analyzed for dosimetry. We found that SD linearly increased with decreasing exposure and was between 0.32 and 0.85%, which is comparable to previous studies . Intra‐film uniformity uIuniformity was evaluated to be between 0.22 and 0.45% by comparing the MPV of small films irradiated to the same dose and coming from the same sheet.…”
Section: Resultssupporting
confidence: 88%
“…The energy dependence of EBT3 film has been studied by various authors. Massillon et al investigated this for 50 kV, 6 MV and 15 MV photon beams. For doses higher than 1 Gy, no significant statistical differences were found between 6 and 15 MV and only small differences (11%) were detected when comparing the 50 kV beam with the megavoltage ones.…”
Section: Introductionmentioning
confidence: 99%
“…This energy dependence (at out‐of‐field energies compared with a primary 6‐MV beam) is small but present. EBT film, for example, was found to under‐respond by up to 8% (for EBT), while EBT2 and 3 were found to overrespond by 5–10% . These effects depend slightly on dose, color channel, and other scan parameters …”
Section: Measurement Approachesmentioning
confidence: 96%
“…The EBT3 is self-developing film in real time, almost energy independent, and near tissue-equivalent [1720]. Film calibration, to correlate the film’s optical density with the absorbed dose, was performed with a 6MV beam from a linear accelerator in the reference conditions (field size of 10×10 cm 2 at the depth of maximum dose (d max ) of 1.4 cm) for 13 different dose levels ranging from 0 to 464 cGy.…”
Section: Methodsmentioning
confidence: 99%